EXPLORING CRITICAL THINKING AT A KAZAKHSTANI HIGHER EDUCATION INSTITUTION: EDUCATORS' PERSPECTIVES, PRACTICES, AND CHALLENGES - Assaubayeva, Nazira (Nazarbayev University Graduate School of Education, 2024)
Critical thinking is recognized globally and locally as an essential skill to be nurtured in higher education. The acquisition of skills contributes to human capital, particularly the workforce’s competitiveness. However, there is limited research on the challenges of teaching critical thinking faced by Kazakhstani educators. This study explores the pedagogical approaches, practices, and challenges of teaching critical thinking through the faculty perspective by conducting interviews in one state university in Kazakhstan. Findings show that faculty members encounter challenges in teaching critical thinking related to the students’ unpreparedness, critical thinking hindering characteristics, and lack of digital tools. Despite these challenges, educators use a variety of critical thinking-fostering strategies such as group work, questioning, writing, and discussion. The result of this study reveals the necessity for a more holistic approach to teaching critical thinking that comprises both skills and dispositions. In order to address this, it is suggested that the skills be taught explicitly and systematically which requires the support of the administration of higher education institutions and decision-makers.
Қазақстандық жоғары оқу орындарының бірінде сыни ойлауды зерттеу: оқытушылардың көзқарастары, практикасы және мәселелері
Keywords: Research Subject Categories::SOCIAL SCIENCES; critical thinking; teacher experience; critical thinking teaching practices; critical thinking teaching obstacles; higher education; Kazakhstan; Type of access: Restricted